STATE PRESENCE AND DEMOCRATIC CULTURE: A SPATIAL INVESTIGATION - Turner, Jacob (Teoria & Pesquisa Revista de Ciência Política, 2020)
The relationship between state presence and individual-level democratic attitudes remains an open line of inquiry long after the third-wave of democratization. While greater access to state resources implies stronger integration into the state’s legality, increased exposure to ineffective or violent state agents can have a toxic effect on notions of citizenship. This article seeks to measure the relationship between perceived access to agents of the state and individual support for democracy as the best form of government. To develop a measure of daily access to street level state organizations such as the police, firefighters, and public healthcare workers, this article uses the geocoded locations of each survey respondent in the Local Democracy Index (Índice de Democracia Local - IDL) of the city of São Paulo. Several different multilevel model specifications suggest that this measure of distance negatively correlates with support for democracy, implying that respondents living closer to state offices are more likely to express pro-democratic views while controlling for important socio-economic characteristics. These results suggest that a higher level of access to state agents and the services they provide could promote certain dimensions of democratic citizenship, though the relationship can be negated when those interactions are mostly violent in nature